Peran Sitokin dan Metabolisme Lipid dalam Stroke - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Cytokines regulate the innate and adaptive immune responses and are pleiotropic, redundant and multifunctional. Expression of most cytokines, including TNF-a and IL- I a/jJ, is very low in normal brain. Metabolism of lipids is of particular interest due to their high concentration in the brain. Inflammatory response after stroke suggests that cytokines (TNF-a, IL-I alfJ, IL-6), affect the phospholipid metabolism and subsequent production ofROS that may potentiate brain injury. Inflammatory responses are instrumental in the formation and destabilization of atherosclerotic plaques. Secretory PLA2 IlA isfound in human atherosclerotic lesions and is implicated in initiation, progression and maturation of atherosclerosis, a riskfactor for stroke. Lipoprotein-PLA2, part of apolipoprotein B- I 00 of LDL, plays a role in vascular inflammation and coronary endothelial dysfUnction. Cytokine antagonism attenuated secretory PLA2 IlA actions, suggesting cytokine-lipid integration studies wi/Nead to new concepts contributing to bench-to-bedside transition for stroke therapy.